The sanctuary's imperial architectural development, conflict with Christianity, and final days - White, Donald (Extramural sanctuary of Demeter and Persephone at Cyrene, Libya. Final reports, 2012)
Cover; Contents; List of Illustrations; Minor Abbreviations; Abbreviations and Bibliography; Acknowledgments; Introduction; I: Part 1: Background to the Early Imperial Period; Part 2: The Early Imperial Walled Remains, 31 B.C.-A.D. 115; II: Part 1: Sanctuary Development from A.D. 115-262; Part 2: Building Alterations before the A.D. 262 Earthquake; III: Part 1: Background to the Years A.D. 262-365; Part 2: The Sanctuary's Final Construction; Part 3: Squatter Period Walls; IV: Part 1: Sanctuary Iconclasm; Part 2: Similar Activities Outside the Region.